The Effect of Mental Significance In Demonstrating The Clarity of The Concept of Consideration By People Mono Theism And Justice. (Journal of the College of Basic Education, 2025)
Mutazila is one of the Islamic currents that follow logical evidence and work to consolidate it in the minds of those who follow their fundamentalist beliefs differ from others in that they glorify mental evidence but this glorification is not intended to sedition and to deviate from what the Islamic doctrines and currents agreed on because it is one of the rejected things that the beholder does not adopt they have the fact that this Leads to corruption in religion and consideration and makes it abasic for knowing the depth of significance of the speech unprecedented linguist with a necessary knowledge and requires a retrate in the costly, beholder when looking to be scientist of what is talking about with the availability of reasoning based on logical evidence the concept of looking at them is realized when the beholder knows and knows how to address him mental significance lies in proving the concept of looking when it is a path to learn the secrets of the Linguisticl, Between the meaning and connotation and they go further that should be considered is to have relationship and this applies on the issue of assignment they require mental ability to indicate the underlying meaning and its clarity because beholder has them when completed from a mental point of view, He was able to find out the depth of the meaning of the text with a complete departure from tradition in realizing the concept of looking if they in traduce it to tradition because departing from it urges the beholder to think infer and this comes only by looking.